Cerclage for sonographic short cervix in singleton gestations without prior spontaneous preterm birth: systematic review and meta‐analysis of randomized controlled trials using individual patient‐level data - Berghella, V.; Ciardulli, A.; Rust, O. A.; To, M.; Otsuki, K.; Althuisius, S.; Nicolaides, K. H.; Roman, A.; Saccone, G. (Ultrasound in obstetrics & gynecology, 2017)
ABSTRACT Objective The aim of this systematic review and meta‐analysis was to quantify the efficacy of cervical cerclage in preventing preterm birth (PTB) in asymptomatic singleton pregnancies with a short mid‐trimester cervical length (CL) on transvaginal sonography (TVS) and without prior spontaneous PTB. Methods Electronic databases were searched from inception of each database until February 2017. No language restrictions were applied. All randomized controlled trials (RCTs) of asymptomatic singleton pregnancies without prior spontaneous PTB, found to have short CL < 25 mm on mid‐trimester TVS and then randomized to management with either cerclage or no cerclage, were included. Corresponding authors of all the included trials were contacted to obtain access to the data and perform a meta‐analysis of individual patient‐level data. Data provided by the investigators were merged into a master database constructed specifically for the review. Primary outcome was PTB < 35 weeks. Summary measures were reported as relative risk (RR) with 95% CI. The quality of the evidence was assessed using the GRADE approach. Results Five RCTs, including 419 asymptomatic singleton gestations with TVS‐CL < 25 mm and without prior spontaneous PTB, were analyzed. In women who were randomized to the cerclage group compared with those in the control group, no statistically significant differences were found in PTB < 35 (21.9% vs 27.7%; RR, 0.88 (95% CI 0.63–1.23); I2 = 0%; five studies, 419 participants), < 34, < 32, < 28 and < 24 weeks, gestational age at delivery, preterm prelabor rupture of membranes (PPROM) and neonatal outcomes. In women who received cerclage compared with those who did not, planned subgroup analyses revealed a significantly lower rate of PTB < 35 weeks in women with TVS‐CL < 10 mm (39.5% vs 58.0%; RR, 0.68 (95% CI, 0.47–0.98); I2 = 0%; five studies; 126 participants) and in women who received tocolytics (17.5% vs 32.7%; RR, 0.54 (95% CI, 0.31–0.93); I2 = 0%; four studies; 169 participants) or antibiotics (18.3% vs 31.5%; RR, 0.58 (95% CI, 0.33–0.98); I2 = 0%; three studies; 163 participants) as additional therapy to cerclage. The quality of evidence was downgraded two levels because of serious imprecision and indirectness, and therefore was judged as low. Conclusions In singleton gestations without prior spontaneous PTB but with TVS‐CL < 25 mm in the second trimester, cerclage does not seem to prevent preterm delivery or improve neonatal outcome. However, in these pregnancies, cerclage seems to be efficacious at lower CLs, such as < 10 mm, and when tocolytics or antibiotics are used as additional therapy, requiring further studies in these subgroups. Given the low quality of evidence, further well‐designed RCTs are needed to confirm the findings of this study. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd. Resumen Cerclaje para el cérvix corto observado mediante ecografía en gestaciones con feto único sin parto pretérmino espontáneo previo: revisión sistemática y metaanálisis de ensayos controlados aleatorizados utilizando datos individuales de pacientes Objetivo El objetivo de esta revisión sistemática y metaanálisis fue cuantificar la eficacia del cerclaje cervical en la prevención del parto pretérmino (PPT) en embarazos asintomáticos de feto único con una longitud cervical (LC) corta a mitad de trimestre observada en la ecografía transvaginal (ETV) y sin PPT espontáneo previo. Métodos Se buscó en bases de datos electrónicas desde el inicio de cada base de datos hasta febrero de 2017. No se aplicaron restricciones de idioma. Se incluyeron todos los ensayos controlados aleatorizados (ECA) de embarazos asintomáticos con feto único y sin PPT espontáneo previo que en la ETV de mitad de trimestre presentaron una LC corta <25 mm y luego fueron asignados al azar al manejo con cerclaje o sin cerclaje. Se contactó a los autores de correspondencia de todos los ensayos incluidos para solicitar el acceso a los datos y llevar a cabo un metaanálisis de los datos individuales de las pacientes. Los datos proporcionados por los investigadores se agregaron a una base de datos maestra creada específicamente para esta revisión. El resultado primario fue el PPT < 35 semanas. Las medidas resumen se reportaron como el riesgo relativo (RR) con IC 95%. La calidad de la evidencia se evaluó utilizando el planteamiento GRADE. Resultados Se analizaron cinco ECA, que incluían 419 gestaciones asintomáticas de feto único con ETV‐LC <25 mm y sin PPT espontáneo previo. En las mujeres que fueron asignadas al azar al grupo de cerclaje, en comparación con el grupo control, no se encontraron diferencias estadísticamente significativas ni en el PPT de <35 (21,9% vs. 27,7%, RR 0,88 (IC 95% 0,63–1,23), I2 = 0%; cinco estudios; 419 participantes), <34, <32, <28 y <24 semanas, ni en la edad gestacional en el momento del parto, en la rotura prematura de membranas (PPROM, por sus siglas en inglés) o en los resultados neonatales. En las mujeres a quienes se les hizo cerclaje (en comparación con las que no se les hizo), los análisis planificados de subgrupos revelaron una tasa significativamente menor de PPT <35 semanas en mujeres con ETV‐CL <10 mm (39,5% vs. 58,0%, RR 0,68 (IC 95%, 0,47–0,98), I2 = 0%; cinco estudios; 126 participantes) y en las mujeres que recibieron tocolíticos (17,5% vs. 32,7%, RR 0,54 (IC 95%: 0,31–0,93), I2 = 0%; cuatro estudios; 169 participantes) o antibióticos (18,3% vs. 31,5%, RR 0,58 (IC 95%, 0,33–0,98), I2 = 0%; tres estudios; 163 participantes) como terapia adicional al cerclaje. La calidad de la evidencia se rebajó en dos niveles debido a la alta imprecisión y por ser de tipo indirecto, y por lo tanto se juzgó como baja. Conclusiones En gestaciones con feto único y sin PPT espontáneo previo pero con ETV‐LC <25 mm en el segundo trimestre, el cerclaje no parece prevenir el parto pretérmino ni mejorar el resultado neonatal. Sin embargo, en estos embarazos, el cerclaje parece ser eficaz en LC inferiores, como las <10 mm, y cuando se usan tocolíticos o antibióticos como terapia adicional, lo que requiere estudios adicionales en estos subgrupos. Dada la baja calidad de la evidencia, hacen falta más ECA bien diseñados para confirmar los hallazgos de este estudio. 摘要 在无自发性早产既往史的单胎妊娠中超声提示宫颈缩短时行宫颈环扎术:采用个体患者水平资料进行随机对照试验的系统评价和meta分析 目的 本篇系统评价和meta分析的目的是量化在无症状单胎妊娠中宫颈环扎术预防早产(preterm birth,PTB)的效果,这些单胎妊娠孕中期经阴道超声(transvaginal sonography,TVS)提示宫颈长度(cervical length,CL)缩短且无自发性PTB既往史。 方法 检索电子数据库,检索时间从每个数据库建库起至2017年2月。无语种限制。纳入所有无自发性PTB既往史的无症状单胎妊娠的随机对照试验(randomized controlled trials,RCTs),这些单胎妊娠孕中期经TVS发现CL缩短(<25 mm),之后随机分配接受或不接受宫颈环扎术治疗。与所有纳入试验的通信作者取得联系,获取资料,并对个体患者水平资料进行meta分析。将研究人员提供的资料合并到为评价专门建立的主数据库中。主要结局为孕35周前PTB。将综合检测结果表示为相对危险度(relative risk,RR)和95% CI。采用GRADE方法评估证据质量。 结果 对5项RCTs进行分析,其中包括419例TVS‐CL<25 mm、无自发性PTB既往史的无症状单胎妊娠。随机分至宫颈环扎组的孕妇与对照组孕妇相比,孕35周前[21.9%和27.7%;RR,0.88(95% CI 0.63~1.23);I2=0%;5项研究,419例研究对象]、孕34周前、孕32周前、孕28周前和孕24周前PTB,分娩孕周,早产胎膜早破(preterm prelabor rupture of membranes,PPROM)以及新生儿结局无统计学差异。接受宫颈环扎术的孕妇与未接受宫颈环扎术的孕妇相比,预定亚组分析显示,TVS‐CL<10 mm的孕妇[39.5%和58.0%;RR,0.68(95% CI,0.47~0.98);I2=0%;5项研究;126例研究对象]以及除宫颈环扎术外接受宫缩抑制剂[17.5%和32.7%;RR,0.54(95% CI,0.31~0.93);I2=0%;4项研究;169例研究对象]或抗生素[18.3%和31.5%;RR,0.58(95% CI,0.33~0.98);I2=0%;3项研究;163例研究对象]辅助治疗的孕妇孕35周前PTB发生率明显降低。由于高度不精确性和间接性,证据质量降低两级,因此为低质量证据。 结论 在无自发性PTB既往史但孕中期TVS‐CL<25 mm的单胎妊娠中,宫颈环扎术似乎不能预防早产或改善新生儿结局。然而在这些孕妇中,宫颈环扎术在CL缩短(如<10 mm)时以及采用宫缩抑制剂或抗生素作为辅助治疗时似乎有效,需要对这些亚组进行进一步研究。由于证据质量较低,需要进行进一步精心设计的RCTs来证实本研究的结果。 This article's has been translated into Spanish and Chinese. Follow the links from the to view the translations.